2019
DOI: 10.5430/ijba.v10n2p96
|View full text |Cite
|
Sign up to set email alerts
|

The Examination of Factors Influencing Saudi Small Businesses’ Social Media Adoption, by Using UTAUT Model

Abstract: Social media is becoming a major development in electronic commerce among a wide range of sectors, for example, education, government, health care, and business. In Saudi Arabia, a major movement toward social media has taken place, especially among small business entrepreneurs, due to its low cost and the powerful role it can play in globalization.The goal of this paper is to add to the theoretical knowledge base regarding the adoption of social media among Saudi small businesses, by applying the Unified Theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
8
12
0
Order By: Relevance
“…The findings of this study shows that PE has a direct positive effect on the behavioral intention the adoption of e-marketplace among MSMEs, p < 0.05 and t-statistic = 2.617 > 1.960. The significant effect was in accordance with the results found by Venkatesh et al [9], Mursalin and Al [13] and Humaid and Ibrahim [14] which indicates that there is a strong influence between PE on BI in using a system. Thus, the hypothesis is accepted.…”
Section: Hypothesis Testingsupporting
confidence: 90%
“…The findings of this study shows that PE has a direct positive effect on the behavioral intention the adoption of e-marketplace among MSMEs, p < 0.05 and t-statistic = 2.617 > 1.960. The significant effect was in accordance with the results found by Venkatesh et al [9], Mursalin and Al [13] and Humaid and Ibrahim [14] which indicates that there is a strong influence between PE on BI in using a system. Thus, the hypothesis is accepted.…”
Section: Hypothesis Testingsupporting
confidence: 90%
“…Results of facilitating conditions coincide with findings of prior studies that have examined the impact of facilitating conditions on the intention to use (e.g. Engler and Alpar 2018) and actual use (Chua et al 2018;Salahshour Rad et al 2019;Humaid and Ibrahim 2019) of social media. Findings of the study are also like Al-Azawei (2018) who reported the importance of facilitating conditions in actual Facebook use in the context of Iraq.…”
Section: Influence Of Facilitating Conditions On the Adoption And Use...supporting
confidence: 85%
“…Likewise, prior research (e.g. Humaid and Ibrahim 2019) empirically supported the assertion regarding the influence of social influence on behaviour intention for using social media, even though others found the opposite (Gan, Li and Liu 2017). As academic libraries that feel more pressure from others to use social media are more likely to do so (Yuvaraj 2016), social influence is expected to predict the intention to use social media in academic libraries in Ghana.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 66%
See 2 more Smart Citations